THE RELATIONSHIP BETWEEN SELF-EFFICACY AND INTEREST OF ENTREPRENEURS AMONG FAMILY WELFARE EDUCATION STUDENTS, SYIAH KUALA UNIVERSITY - Maryam, Siti; Nurbaiti, Nurbaiti; Fitriana, Fitriana; dewi, rosmala; jannah, izzatul (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2022)
An entrepreneur needs to be emphasized courage and confidence to start. That is one of the factors that influence the interest in entrepreneurship, namely self-efficacy. In everyday life, self-efficacy is very influential in increasing interest in entrepreneurship among students, which will affect individuals in determining actions to achieve the expected goals. This study aims to identify the level of self-efficacy and the level of interest in entrepreneurship and to determine the relationship between self-efficacy and interest in entrepreneurship of students majoring in family welfare education (PKK) FKIP Syiah Kuala University. This study used a sample of 36 students who were already entrepreneurs from the PKK FKIP Study Program, Syiah Kuala University and the research was conducted in May 2022 - June 2022. The results showed that, in general, the level of self-efficacy of students majoring in PKK FKIP Syiah Kuala University was included in the high category, namely 64%. However, in detail the level of self-efficacy is more dominant in the magnitude indicator (difficulty level) with a high category of 86.1%. The level of entrepreneurial interest of students majoring in PKK FKIP is also generally included in the high category, namely 73%, if in more detail the level of interest in entrepreneurship is more dominant in intrinsic factors with a high category of 70%. Based on the results of the correlation test between self-efficacy and entrepreneurial interest, it shows that there is a positive relationship between the two variables, the value of r_xy = 0.55, meaning that between the two variables has a moderate relationship, with a significant value of 0.001 <0.05, it means that there is a significant positive relationship between the two variables, self-efficacy and entrepreneurial interest in PKK FKIP students at Syiah Kuala University.